Educating Mats: Encountering Finnish 'lads' and Paul Willis's Learning to Labour in Sweden. (December 2018) - Trondman, Mats
In this paper the author himself tells an auto-ethnographical tale about how he came to read and understand Paul Willis's Learning to Labour (1977) in the late 1970s as a 22-year-old non-qualified junior high school teacher of Finnish 'lads' whose parents had come to Sweden as industrial workers in the late 1960s and early1970s. While most of these 'lads' came to reproduce class, the author himself continued to higher education to become a 'class traveller'. Hence, cultural production and cultural autonomy can work in more than one way, even at the very same time.